Molecular dynamics simulations of orientation induced interfacial enhancement between single walled carbon nanotube and aromatic polymers chains. (June 2015) - Yu, Bowen; Fu, Sirui; Wu, Zhiqiang; Bai, Hongwei; Ning, Nanying; Fu, Qiang
Abstract: In this work, molecular dynamics simulations were utilized to probe the interfacial enhancement between aromatic polymers and single walled carbon nanotube (SWCNT) induced by molecular orientation. Two aromatic polymers, polyphenylene sulfide (PPS) and polystyrene (PS) were chosen for comparison study. It was found that orientation of polymer chain could bring about an obvious promotion in interfacial interaction for both systems. In PPS/SWCNT systems, the increased interfacial interaction energy was due to the easy formation of offset π–π stacking, while in PS/SWCNT systems the formation of edge-to-face π–π stacking contributed to the enhancement. Polymer/SWCNT composites were also constructed and a similar interfacial enhancement was observed as well. The mechanism of the orientation induced enhancement was a combination of forming more π–π stacking and better coating effect. This will help to deepen the understanding of interfacial interaction in aromatic polymers/carbon nanotubes composites and guide the fabrication of high performance materials.